Prohibition of Quran Interpretation in Hadith: Perspectives from Majelis Tafsir Al-Qur'an in North Sumatra - Zulfirman Manik; Muhammad Ismailsyah Sembiring (Getpress Management Journals, 2025)
The da'wah movement carried out by the Majelis Tafsir Al-Qur’an (MTA) has shown significant development, but this development is inseparable from the rejection of the community, especially against the MTA of North Sumatra. The rejection by the community is based on the existence of the Prophet's hadith which prohibits interpreting the Quran. The community's view that MTA has violated the command contained in the hadith. This research discusses the view of the MTA congregation on the hadith of the prohibition of interpreting the Quran. To understand the theme, this study asks the question of how the views of the MTA representatives on the hadith of the prohibition of interpreting the Quran. To answer the research question, qualitative research method is used with the approach of interview, observation, and documentation. The source of data comes from pilgrims who are members of the MTA. Data analysis is done by data collection, data reduction, and data presentation. The findings of this study explain that the view of the MTA Representative of the hadith of the prohibition of interpreting the Quran is contextualist. The prohibition of interpreting the Qur'an in question is interpreting the Qur'an with the mind that follows lust without following the applicable rules. Finally, it can be emphasized that the view of the MTA on the hadith of the prohibition of interpreting the Qur'an is in accordance with the explanation of the scholars of hadith. So that this can make a good contribution to the community in order to avoid negative assumptions about the MTA representatives that have occurred so far, and can maintain good Muslim brotherhood.